2019
DOI: 10.31234/osf.io/42t6e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are sexual desire and sociosexual orientation related to men’s salivary steroid hormones?

Abstract: Objective: Although it is widely assumed that men’s sexual desire and interest in casual sex (i.e., sociosexual orientation) are linked to steroid hormone levels, evidence for such associations is mixed. Methods: We tested for both longitudinal and cross-sectional relationships between salivary testosterone, cortisol, reported sexual desire and sociosexuality in a sample of 61 young adult men, each of whom was tested weekly on up to five occasions. Results: Longitudinal analyses showed no clear relationships b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, no differences have been observed in women's brain responses with regard to the attraction of men (4). However, other studies demonstrated an increase in testosterone and cortisol in women who watched attractive men and men who looked at attractive women (5,6). Thus the attractiveness is significantly related to sexual hormones (6).…”
mentioning
confidence: 89%
“…On the other hand, no differences have been observed in women's brain responses with regard to the attraction of men (4). However, other studies demonstrated an increase in testosterone and cortisol in women who watched attractive men and men who looked at attractive women (5,6). Thus the attractiveness is significantly related to sexual hormones (6).…”
mentioning
confidence: 89%
“…More precisely, lower voice pitch is linked to higher testosterone levels in men (Aung & Puts, 2020) and testosterone administration lowers voice pitch in biological females (Huang et al, 2015;Irwig, Childs, & Hancock, 2016). Further, higher testosterone has been linked to more unrestricted sociosexual orientation in women (Shirazi et al, 2019) and men (but only when cortisol levels are low; Stern et al, 2020a;Puts et al, 2015). Yet, it remains unclear whether individual differences in testosterone levels could potentially be a common cause explaining an association between voice pitch and sociosexual orientation (including all three facets).…”
Section: Voice Pitch and Self-reported Sociosexual Orientationmentioning
confidence: 99%